Konsep dan Teori Belajar dalam Perspektif Pendidikan Islam - Yusuf Yusian Septianto Saleh; Bilqis Fatimatus Arifiani (Fakultas Agama Islam, Universitas Hasyim Asy'ari Tebuireng Jombang, 2024)
Education is an individual's conscious effort and effort to develop themselves to the potential they have. Education is fundamental capital for individuals because with education, individuals will be able to find solutions to every problem they encounter. In Islam, education is mandatory for Muslims. Because with education, a servant will know and walk towards Allah SWT. The objectives of this research are 1) to understand the concepts and theories of learning from an Islamic education perspective; 2) explain learning methods in Islamic education; 3) analyze the challenges in Islamic education. The method used in writing this article uses library research which focuses on collecting data through several references such as literature, books, notes and published scientific information. The research results show that there are three types of learning concepts and theories from an Islamic education perspective, namely taqlid (imitation), tajribah wal khata' (trial and error), and ta'wid (habituation). In Islamic education learning methods there are five methods, namely lecture, discussion, question and answer, experiment, and demonstration. Islamic education faces various challenges, including: identity crisis, global education climate, and changes in the national education system, so skills are needed that must be improved by being able to find solutions, think critically, and have high creativity.